How Maritime Education and Training (MET) Instructors Address Assessment Protocol - Rogin, James (Global Oceans 2020: Singapore – U.S. Gulf Coast, 2020)
With the advent of more technologies being utilized on a modern Ships Navigational Bridge it is important to address all human elements that play a role in the safety of the vessel. Of these elements, the training of personal in the use of the ships modern equipment is imperative. To address this, the maritime industry both on the international and national levels implements a series of assessments to validate a potential officer's knowledge base. This study looks to identify the Maritime Bridge Simulators instructor's interpretation of the assessments done on a Navigation simulator. An Auto Ethnographic approach is utilized to highlight current and previous interactions with the former Mariners, who are now educators. These Maritime Education and Training (MET) instructors, who utilize a modern Full Mission Bridge Simulator, as they assess a navigational bridge team will be examined. The preliminary understanding and projected findings is that both the performance based assessment and the interactive assessments done on these simulators, inform teaching and enhance learning experiences. However, the assessments themselves which are mandated, are vague and unsuccessful in properly assessing a future Maritime Officer. As Mariners have all experienced some subject matter experts who may have all of the qualifications needed to teach, yet are incapable of doing so. On the other hand, some may not have mastery of the subject but are able to pass on the knowledge needed for one to succeed sufficiently. In a worst-case scenario, there are those who "can neither do nor teach." How can we prevent these instances from offering? Is there something within mandated regulations that can be used to avoid this from occurring? Could there be a cultural or societal aspect that we can use as a preventative means? These questions are difficult to answer. There is a need to be judged on many levels, as well as discussed and debated. Instructors in the Maritime industry are no different than the Instructors in other fields. They have all been exposed to the subject that they are required to teach, how they prepare and interpret the lessons needed is not always the same as one would think. Simulation as an educational tool has been used across a broad spectrum of subjects and industries. How these simulations are integrated within the classroom differs depending on the simulator. One of the main objectives of simulation is Project-Based learning. Simulations that encompass the Project-Based Learning design can be defined as complex tasks based on difficult questions. These situations provoke the student to design, implement problem-solving, and decision making processes. The fact-finding activities embedded in the simulation can provide students with situations where they need to work independently over significant periods. At the end of the simulation, there is a concluding event that emulates realistic products or situations [1]. In addition to the "Project" associated with this theory, there are other defining factors; these factors include authentic content, authentic assessment, teacher facilitation, and clear educational goals[2]. All of these play a significant role within the realm of Maritime Simulation. For a successful Simulation of a Ships Navigational bridge to occur, the preliminary understanding and projected findings is that the performance-based assessment and the interactive assessments done on these simulators, inform teaching and enhance learning experiences. In order to accomplish this, many challenges are facing the educators that operate these simulated exercises. The first challenge is the Professional Development of the educators. Unlike most professional educators, the requirements to teach within this field are limited. The students that these instructors teach also differ in that they are an older student. This method is called Andragogy. The way the instructor approaches this must be different from the Petrological approach of young students. The final challenge addressed here is the instructor's interpretation of both international and national regulations. By utilizing Authentic Assessment, educators need to cultivate a better understanding of the concept or subject taught and focus less on the improved learning outcomes associated with them [3].